This preview shows pages 1–3. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: Laplace Transform Step functions PS April 9, 2011 Problem 1 Find the Laplace transform of g ( t ) = ( t 2 t < 2 6 2 < t < (1) Solution : g ( t ) in terms of the Heaviside function is: g ( t ) = t 2 u 2 ( t )( t 2 6) . Evaluating the two separately, we write L t 2 = 2 s 3 . (2) For the second part we need to use the tshifting theorem: Step 1: f ( t 2) = t 2 6 Step 2: f ( t ) = ( t + 2) 2 6 = t 2 + 4 t 2 Step 3: L u 2 ( t )( t 2 6) = e 2 s L t 2 + 4 t 2 = e 2 s 2 s 3 + 4 s 2 2 s (3) Combining the results: L { g ( t ) } = 2 s 3 + e 2 s 2 s 3 + 4 s 2 2 s . (4) 1 c HF, 2011 Laplace Transform Step functions PS April 9, 2011 Problem 2 Find the inverse Laplace transform of F ( s ) = e 2 s s 2 + s 2 (5) Solution : We can either perform do partial fractions, or complete the square here. Lets do the latter: F ( s ) = e 2 s ( s + 1 2 ) 2 9 4 (6) For the second part we need to use the tshifting theorem: Step 1: L 1 1 ( s + 1 2 ) 2 9 4 = 2 3 L...
View
Full
Document
This note was uploaded on 05/02/2011 for the course GE 207K taught by Professor None during the Spring '10 term at University of Texas at Austin.
 Spring '10
 None

Click to edit the document details